Bipolar VLSI - an application for a high performance microcontroller - Jones, Peter L. (Zielona Góra: Uniwersytet Zielonogórski)
This paper looks at the special merits of bipolar differential logic for high performance VLSI. A design route is developed using a high level hardware description language leading to a semi custom style of automatic layout. Preliminary assessment from simulation suggests that 100MHz operation of an eight-bit high-functionality microcontrol1er can be achieved using this approach.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka